Effect of cinnamaldehyde and 1, 8-cineole on performance, egg quality and some blood parameters of laying hens - CIMRIN, TULAY (The Indian Journal of Animal Sciences, 2019)
This study was aimed at determining the effects of the addition of cinnamaldehyde and 1, 8-cineole to laying hen rations on performance, egg quality and some blood parameters. For this purpose, 96 (48-week-old and initial body weight average 1,773.19 g) laying hens of the Bovans White lineage were used. Birds were fed on a standard basal ration (PC) and basal rations were added with 500 mg/kg of antibiotic (NC); 100 mg/kg of cinnamaldehyde (T1); and 100 mg/kg of 1, 8-cineole (T2) for 60 days. While the feed consumption levels of groups T1 and T2 were significantly lower than that of group PC, their egg production was significantly lower than that of groups PC and NC. When compared to groups PC and NC, it was observed that the feed additive given to group T2 had significantly reduced the feed conversion rate. All of the feed additives used in this study were determined to have decreased egg weight, eggshell strength and eggshell thickness, in comparison to the measurements of group PC. Furthermore, when compared to groups PC and NC, groups T1 and T2 were ascertained to have lower serum glucose and cholesterol levels. However, when compared to the other 3 groups, group T1 presented with significantly higher serum aspartate aminotransferase (AST) levels and group T2 displayed a significantly higher rate of defective eggs. In result, the addition of cinnamaldehyde and 1, 8-cineole to the ration was observed to show a positive impact on serum glucose and cholesterol levels, and a negative impact on other performance parameters and eggshell quality. It was concluded that further more detailed investigation is required in this added to laying hen rations.